Los ejercicios relajantes para potenciar el aprendizaje de los niños del nivel inicial ii paralelo “a” sección matutina de la escuela teniente Hugo Ortiz de la ciudad de Loja, período lectivo 2017-2018. - Andrade Salazar, Tatiana del Cisne (2018)
The present investigative work entitled: THE RELAXING EXERCISES TO ENHANCE THE LEARNING OF CHILDREN OF THE INITIAL LEVEL II PARALLEL "A" MORNING SECTION OF THE HUGO ORTIZ LIEUTENANT SCHOOL OF THE CITY OF LOJA, LECTIVE PERIOD 2017-2018, had as general objective to determine the incidence of relaxation exercises to enhance learning in children of the initial level II parallel "A" of the institution mentioned, the type of research was experimental, and the methods used were scientific, analytical-synthetic, inductive, deductive and statistical ; To obtain the information, the observation technique was used, the survey was directed to the teachers of the initial level, and the application of the Basic Function Test with a sample of 21 children investigated, this instrument consists of 15 areas of the which is mentioned below the most representative percentage once the pre-test is applied; in the area of care and fatigue a percentage of 0% equivalent to Disabled is shown, afterwards the application of the proposal was made, which consists of various activities to improve its development in a period of two months to then make an evaluation with the purpose of verifying results before and after the application of the same; in which it is evident within the area of attention and fatigue 81% after applying the post-test equivalent to Enabled. This has allowed us to conclude that relaxing exercises benefit and enhance learning in infants, helping to improve the physical and mental state of children and, therefore, be ready for greater school learning